A dynamic causality test of exports and economic growth in Zimbabwe. (1st January 2012) - Tsaurai, Kunofiwa; Odhiambo, Nicholas M.
In this paper, we examine the causal relationship between export growth and economic growth. The causal relationship between exports and economic growth has been a subject of extensive debate in recent years. There are currently three dominant views regarding the relationship between exports and economic growth. The first view maintains that it is the growth of exports that drives economic growth. The second view argues that it is economic growth that spurs exports expansion; while the third view maintains that both exports and economic growth promote one another. Using the autoregressive distributed lag (ARDL)-bounds testing approach, we find that there is a distinct causal flow from export growth to economic growth in Zimbabwe – both in the short run and in the long run. We therefore recommend that policies, which are geared towards export promotion should be intensified, in order to promote long-term economic growth in Zimbabwe.